Español - Asprilla-Hurtado, Marinella; Estacio-Grueso, Luis; Bermúdez-Quintero, Luis (Boletín de Innovación, Logística y Operaciones, 2023)
<!--StartFragment--> <p class="MsoNormal" style="text-align: justify; line-height: 12.0pt; mso-pagination: widow-orphan; tab-stops: 45.8pt 91.6pt 137.4pt 183.2pt 229.0pt 274.8pt 320.6pt 366.4pt 412.2pt 458.0pt 503.8pt 549.6pt 595.4pt 641.2pt 687.0pt 732.8pt; text-autospace: ideograph-numeric ideograph-other;">The present article aims to showcase the implementation of pedagogical strategies for the Comprehensive Management of Household Solid Waste (GIRSD), contributing to the minimization of negative impacts generated in the tidal zone. The application of these strategies facilitates the environmental education process and, moreover, enhances the potential and adds value to the waste. The study was primarily based on a bibliographical review of topics related to the integrated management of solid waste in tidal zones in Buenaventura, with an emphasis on a qualitative methodological approach. The results obtained focus on the management, separation, utilization, and environmental culture, which are fundamental aspects for implementing an effective Comprehensive Solid Waste Management System (GIRS) that contributes to social and environmental well-being. <!--EndFragment-->